Brain Structural Network Compensation Is Associated With Cognitive Impairment and Alzheimer’s Disease Pathology - Sheng, Xiaoning; Chen, Haifeng; Shao, Pengfei; Qin, Ruomeng; Zhao, Hui; Xu, Yun; Bai, Feng; , the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Neuroscience, 2021)
Background: Structural network alterations in Alzheimer’s disease (AD) are related to worse cognitive impairment. Our aim was to quantify the alterations in gray matter associated with impaired cognition and their pathological biomarkers in AD-spectrum patients. Methods: We extracted gray matter networks from 3D-T1 magnetic resonance imaging scans, and graph theory analysis was used to explore alterations in the network metrics in 34 healthy controls, 70 mild cognitive impairment (MCI) patients and 40 AD patients. Spearman correlation analysis was computed to investigate the relationships among network properties, neuropsychological performance and cerebrospinal fluid pathological biomarkers (i.e., Aβ, t-tau and p-tau) in these subjects. Results: AD-spectrum individuals demonstrated higher nodal properties and edge properties associated with impaired memory function and lower amyloid-β or higher tau level than controls. Furthermore, these compensations at the brain regional level in AD-spectrum patients were mainly in the medial temporal lobe; however, the compensation at the whole-brain network level gradually extended from the frontal lobe to become widely distributed throughout the cortex with the progression of AD. Conclusion: The findings provide insight into the alterations in the gray matter network related to impaired cognition and pathological biomarkers in the progression of AD. The possibility of compensation was detected in the structural networks in AD-spectrum patients, the compensatory patterns at regional and whole-brain levels were different and the clinical significance was highlighted.